PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT. NUSANTARA SURYA SAKTI CABANG TERNATE. - Serifana Tamrin; Asril Arilaha (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2016)
This research aims analyzing the Individual factors and organizational factors together significant influence with employee performance of PT. Nusantara Surya S akti Cabang Ternate. Sample using purposive sampling method is to direct all employees to choose as many as 48 people. Data collection methods used were questionnaires, interviews, and documentation. Data were analyzed with multiple linear regression with the statistical software SPSS 19.0 for windows. Results showed that Individual factors and organizational factors together influence employee performance PT. Nusantara SuryaSakti Cabang Ternate amounted to. Factors that most significantly influence employee performance of PT. Nusantara Surya Sakti Cabang Ternate is the organizational factor amounted to.